Assessment of Male Involvement in Family Planning use in Loka Abaya District, Southern Ethiopia: Cross-Sectional Study (Global Journal of Human-Social Science, 2016)
Background Involving men and obtaining their support and commitment to family planning is of crucial for family planning service utilization But the information available on male involvement in family planning use is limited in study area Objective To assess male involvement in family planning use and associated factors in Loka Abaya woreda sidama zone Ethiopia Method A community based cross sectional study was conducted in Loka Abaya district from Sep 2014 to June in 2015 Systematic random sampling was used to select the study subjects Married men were interviewed to assess the status of male s involvement status in family planning method utilization by using semi-structured interviews Finally data was coded cleaned entered using EPI-info7 software and analyzed using SPSS version 20
Keywords: male involvement; method approval; spousal communication; contraceptive use